Efektivitas Mindfulness Based Intervention : Doa Memohon Kesembuhan terhadap Penurunan Kecemasan Pasien Preoperasi di RS Permata Hati - Alvionita, Prafika; Arya Ramadia dan; Rohmi Fadhli (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
Preoperative anxiety is a psychological response experienced by patients who are about to undergo surgery. If not managed properly, it can affect physiological stability—such as elevated blood pressure and heart rate—which may interfere with the surgical procedure or even result in its cancellation. One approach to reduce anxiety is through a Mindfulness-Based Intervention (MBI) using healing prayer. This technique encourages individuals to be fully present and aware, while prayer provides calmness and emotional comfort. This study aims to determine the effectiveness of Mindfulness-Based Intervention using healing prayer in reducing preoperative anxiety among patients at Permata Hati Hospital. This quasi-experimental study employed a pretest-posttest design with two groups. A total of 32 patients were divided into intervention and control groups using consecutive sampling. Data were analyzed using the Wilcoxon Signed Rank Test. The results show that the intervention significantly reduced preoperative anxiety (p-value = 0.000, < 0.05). In the intervention group, 56.3% of respondents experienced moderate anxiety, with a mean pretest score of 28.63 and a posttest score of 14.63. In contrast, most respondents in the control group (68.8%) experienced severe anxiety, with a mean pretest score of 29.06 and a posttest score of 29.19. The findings indicate that Mindfulness-Based Intervention using healing prayer is effective in reducing preoperative anxiety and may be considered as a complementary method in surgical preparation